STUDY OF BACTERIAL PATHOGENS CAUSING URINARY TRACT INFECTION AND ANTIBIOGRAM PATTERN IN SYMPTOMATIC ADULTS - M, RAVISH KUMAR; N, SHRUTHI (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: Urinary tract infections (UTIs) are most common infection seen in community and hospital. It is important to know the causative agent and antibiotic susceptibility pattern to administer specific treatment and prevent drug resistance. Hence, the present study was conducted to know the most common etiological agent and antibiogram of symptomatic UTIs. Methods: The study was conducted at a tertiary care hospital. All the adult patients presented with symptoms of UTI were involved. As per the standard guidelines, clean catch mid-stream urine sample was collected and inoculated on MacConkey’s agar and blood agar by standard loop technique. The isolates with significant bacteriuria were subjected for Kirby-Bauers’ disk diffusion antibiotic susceptibility testing. Results: One thousand two hundred and fifty symptomatic patients were screened for UTI. A total of 358 organisms were isolated in culture with significant bacteriuria. Among 358, Escherichia coli was commonest organism with 267 (74.5%), followed by Klebsiella species accounting for 52 isolates (14.5%) and Citrobacter species 25 (7.0%), and Pseudomonas aeruginosa 14 (4%). Higher degree of sensitivity was seen with imipenem (90%), amikacin (80%), and gentamycin (78%) followed by nitrofurantoin (75%) for E. coli. Lower degree of sensitivity was noted for norfloxacin (50%), ceftriaxone (62%), cotrimoxazole (56%), and pipericillin-tazobactum (60%). Klebsiella was sensitive to amikacin (74%) and imipenem (80%). Conclusion: In the present study, E. coli was the most common organism causing UTI. Nitrofurantoin can be started as empirical treatment for lower UTI. Gentamycin was found to be equally effective as amikacin so that it can be used instead of amikacin to decrease the selective pressure on amikacin.